The Effectiveness of Instrumental Music Therapy and Self-Hypnosis on Decreasing Blood Pressure Level among Hypertension Patients - Edi Purnomo; Akbar Nur; Rachmawati Rahim; Zulhaini Sartika A. Pulungan (International Journal of Nursing and Health Services (IJNHS), 2020)
Heart and blood vessel disease, including hypertension, are the highest cause of death in the world. Instrumental music and self-hypnosis are choices to achieve a relaxed state and cause stable blood pressure. The study aimed to determine the effectiveness of instrumental music and self-hypnosis therapy to decrease the blood pressure of hypertensive patients. This study employed a quasi experimental design, pre-test and post-test with non-equivalent control group Forty-six patients were recruited and allocated in the experimental group and the control group. The experimental group received the standard pharmacological therapy and combination instrumental music and self-hypnosis therapy. While the control group received the standard pharmacological therapy. Data were analyzed using a paired t-test and independent sample t-test. The results showed significant decrease in systolic blood pressure after instrumental music and self-hypnosis therapy (p = 0.001) and a significant decrease in diastolic blood pressure after the administration instrumental music and self-hypnosis therapy (p = 0.005). Researchers recommend the use of instrumental music and self-hypnosis therapy to reduce the blood pressure of hypertensive patients